2015
DOI: 10.12659/pjr.893831
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Endovascular Treatment for Hepatic Artery Stenosis after Liver Transplantation: The Role of Percutaneous Endovascular Treatment

Abstract: SummaryBackgroundTo retrospectively analyze the outcomes of interventional radiology treatment of patients with hepatic artery stenosis (HAS) after liver transplantation at our Institution.Material/MethodsHepatic artery stenosis was diagnosed and treated by endovascular technique in 8 (2.8%) patients, who underwent liver transplantation between July 2007 and July 2011. Patients entered the follow-up period, during which we analyzed hepatic artery patency with Doppler ultrasound at 1, 3, 6, and 12 months after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The endovascular approach has become an alternative for the treatment of HAS due to its low morbidity, high patency rates similar to those of open surgery[ 10 ], low graft loss, and low mortality rates. Recent retrospective studies have shown that primary stenting may be the first option, with primary assisted patency rates up to 97% within 12 mo and 93% within 24 mo as well as a decrease in the need for reintervention[ 3 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…The endovascular approach has become an alternative for the treatment of HAS due to its low morbidity, high patency rates similar to those of open surgery[ 10 ], low graft loss, and low mortality rates. Recent retrospective studies have shown that primary stenting may be the first option, with primary assisted patency rates up to 97% within 12 mo and 93% within 24 mo as well as a decrease in the need for reintervention[ 3 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Operative intervention, re-transplantation or endovascular therapy may be a solution to HAS, and early detection is crucial to successful treatment [49]. …”
mentioning
confidence: 99%
“…Significant hepatic artery stenosis (HAS) after liver transplantation (LT) is thought to predispose patients to hepatic artery thrombosis, biliary complications and graft loss, which are associated with poor patient survival [ 1 3 ]. Operative intervention, re-transplantation or endovascular therapy may be a solution to HAS, and early detection is crucial to successful treatment [ 4 9 ].…”
mentioning
confidence: 99%